The Spatial Predilection for Early Esophageal Squamous Cell Neoplasia: A "Hot Zone" for Endoscopic Screening and Surveillance. Issue 15 (April 2016) - Wang, Wen-Lun; Chang, I.-Wei; Chen, Chien-Chuan; Chang, Chi-Yang; Lin, Jaw-Town; Mo, Lein-Ray; Wang, Hsiu-Po; Lee, Ching-Tai
Abstract : Abstract: Early esophageal squamous cell neoplasias (ESCNs) are easily missed with conventional white-light endoscopy. This study aimed to assess whether early ESCNs have a spatial predilection and the patterns of recurrence after endoscopic treatment. We analyzed the circumferential and longitudinal location of early ESCNs, as well as their correlations with exposure to carcinogens in a cohort of 162 subjects with 248 early ESCNs; 219 of which were identified by screening and 29 by surveillance endoscopy. The circumferential location was identified using a clock-face orientation, and the longitudinal location was identified according to the distance from the incisor. The most common circumferential and longitudinal distributions of the early ESCNs were found in the 6 to 9 o'clock quadrant (38.5%) and at 26 to 30 cm from the incisor (41.3%), respectively. A total of 163 lesions (75%) were located in the lower hemisphere arc, and 149 (68.4%) were located at 26 to 35 cm from the incisor. One hundred eleven (51%) early ESCNs were centered within the "hot zone" (i.e., lower hemisphere arc of the esophagus at 26 to 35 cm from the incisor), which comprised 20% of the esophageal area. Exposure to alcohol, betel nut, or cigarette was risk factors for the development of early ESCNs in the lower hemisphere. After complete endoscopic treatment, the mean annual incidence of metachronous tumors was 10%. In addition, 43% of the metachronous recurrent neoplasias developed within the "hot zone." Cox regression analysis revealed that the index tumor within the hot zone (hazard ratio [HR]: 3.19; 95% confidence interval [CI]: 1.17–8.68; P  = 0.02) and the presence of numerous Lugol-voiding lesions in the esophageal background mucosa were independent predictors for metachronous recurrence (HR: 4.61; 95% CI: 1.36–15.56; P  = 0.01). We identified a hot zone that may be used to enhance the detection of early ESCNs during endoscopic screening and surveillance, especially in areas that lack resources and have a high prevalence of ESCNs.